The Power of Connection: How Travel Vlogs Foster Emotional Engagement Leading to Increased Interest in Sri Lankan Heritage Tourism - Prabuddha, Charith; Dangalla, D.K.T.; Jayasinghe, T.; Amarasinghe, T.W.G.M.R.; Lakshan , S. (Journal of Emerging Management Studies, 2025)
Purpose –  This study analyzes how travel vlogs (TV) influence the intention to travel (IT) for historical tourism in Sri Lanka, with an emphasis on the mediating effect of emotional connection (EC). It aims to address gaps in understanding the unique processes through which TV effects travel decisions in cultural contexts, notably within Sri Lanka’s rich heritage tourism environment.Design/methodology/approach – A quantitative study approach was adopted, employing an online survey delivered to 384 prospective historical visitors, as per Morgan’s sample table. Partial Least Squares Structural Equation Modeling (PLS-SEM) evaluated the links between TV, EC, and IT. Structured questionnaires with Likert-scale items assessed variables, assuring reliability and validity through rigorous pilot testing and statistical validation.Findings – The results indicated a large direct association between travel vlogs and intention to visit heritage places, plus a partial mediation impact of emotional connection. Emotional involvement produced by travel vlogs evolved as a fundamental method through which virtual experiences convert into physical travel motives.Conclusion – Travel vlogs dramatically improve interest in Sri Lanka’s historical tourism by encouraging emotional involvement. The immersive storyline and cultural authenticity represented in TV shows provoke feelings like amazement and curiosity, which drive travel decisions.Implications – Tourism authorities and heritage site managers could cooperate with travel vloggers to co-create real, emotionally evocative material. Strategies include educating vloggers in cultural storytelling, incorporating interactive virtual tours, and utilizing social media for targeted advertising. Such activities can increase Sri Lanka’s cultural attractiveness and attract experience visitors.Originality/value – This study pioneers the examination of TV’s influence on historic tourism in Sri Lanka, stressing emotional connection as a mediator is an underexplored topic in previous literature. By contextualizing findings inside a nation famous for cultural legacy, it gives concrete insights for destination marketing and improves theoretical frameworks on media-driven travel motivation.